2022
DOI: 10.3390/ijms232213701
|View full text |Cite
|
Sign up to set email alerts
|

Chalcogen Bond as a Factor Stabilizing Ligand Conformation in the Binding Pocket of Carbonic Anhydrase IX Receptor Mimic

Abstract: It is postulated that the overexpression of Carbonic Anhydrase isozyme IX in some cancers contributes to the acidification of the extracellular matrix. It was proved that this promotes the growth and metastasis of the tumor. These observations have made Carbonic Anhydrase IX an attractive drug target. In the light of the findings and importance of the glycoprotein in the cancer treatment, we have employed quantum–chemical approaches to study non-covalent interactions in the binding pocket. As a ligand, the ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 93 publications
0
6
0
Order By: Relevance
“…A relevant number of papers dealing with this enzyme, its inhibitors, activators and involvement in various diseases have been published in 2022 in this journal [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. The first group of contributed materials dealt with the use of this protein for investigations of basic biochemical approaches, such as protein folding [ 7 ], thermodynamic parameters assessment for protein–ligand interactions [ 8 ], bioluminescence resonance energy transfer connected to the binding of the metal ion to apoenzymes [ 9 ], the possibility to evidence chalcogen bonds in the X-ray crystal structures of CA–lig and adduct [ 10 ]. In two other papers, the role of CAs in CO 2 sequestration processes for alleviating global warming [ 11 ] or in photosynthesis in bacteria and plants (only the α-class CAs were considered in a very informative review by De Simone’s group [ 12 ]) were thoroughly discussed, proving again the potential environmental applications of these enzymes.…”
Section: State Of the Artmentioning
confidence: 99%
“…A relevant number of papers dealing with this enzyme, its inhibitors, activators and involvement in various diseases have been published in 2022 in this journal [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. The first group of contributed materials dealt with the use of this protein for investigations of basic biochemical approaches, such as protein folding [ 7 ], thermodynamic parameters assessment for protein–ligand interactions [ 8 ], bioluminescence resonance energy transfer connected to the binding of the metal ion to apoenzymes [ 9 ], the possibility to evidence chalcogen bonds in the X-ray crystal structures of CA–lig and adduct [ 10 ]. In two other papers, the role of CAs in CO 2 sequestration processes for alleviating global warming [ 11 ] or in photosynthesis in bacteria and plants (only the α-class CAs were considered in a very informative review by De Simone’s group [ 12 ]) were thoroughly discussed, proving again the potential environmental applications of these enzymes.…”
Section: State Of the Artmentioning
confidence: 99%
“…In order to describe the quantum nature of nuclei, Path Integral Molecular Dynamics (PIMD) was developed [ 6 , 35 ]. The method was successfully applied in our numerous studies of intra- and intermolecular interactions [ 23 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is now well established that theoretical methods are an efficient multipurpose tool for chemistry, biochemistry, and material science. Recent scientific efforts have shown that they can help us understand various phenomena, for example, reaction mechanisms or reactivity [ 35 , 36 , 37 , 38 ], electron density distribution [ 39 , 40 , 41 ], and elusive structure of complex biochemical systems or radical centers [ 42 , 43 , 44 ], anticancer [ 35 , 45 ] and antioxidant properties [ 46 , 47 , 48 , 49 , 50 , 51 ], soot formation [ 52 ] or pesticide decomposition [ 53 ]. The exchange coupling between paramagnetic centers has been a subject of such investigations at the density functional theory (DFT) and ab initio levels, but these studies were mainly limited to the interaction between metallic centers [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ].…”
Section: Introductionmentioning
confidence: 99%